Phase I trials of antitumour agents: fundamental concepts - Toloi, Diego de Araujo (Ecancermedicalscience, 2015)
Phase I trials are an important step in the development of new drugs. Because of the advancing knowledge of cancer’s molecular biology, these trials offer an important platform for the development of new agents and also for patient treatment. Therefore, comprehension of their peculiar terminology and methodology are increasingly important. Our objectives were to review the fundamental concepts of phase I designs and to critically contextualise this type of study as a therapeutic option for patients with refractory cancer.